Character or context: What explains behavioural dishonesty in low-income countries? - Ines A. Ferreira; Sam Jones; Jorge Mouco (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We run a lab-in-the-field experiment with 1,060 university students in Mozambique to examine the correlates of behavioural dishonesty, distinguishing between intrinsic and extrinsic factors. Using an incentivized dice game, which yields direct estimates of the propensity to cheat, we find that the effects of demographic and personality traits (e.g., gender, work ethic) generally run in the opposite direction to previous studies. Contingent situational factors, including temperature, humidity, and the number of participants in the room, are associated with large differences in dishonesty-for example, on warm and humid days the predicted cheating rate increased by 14 percentage points. However, in line with theories of trait activation, these extrinsic effects are highly heterogeneous and interact with intrinsic factors, which we believe constitutes an important area for further research.
Keywords: C91; D91; O12; 330; cheating; dice game; dishonest behaviour; Mozambique; personality traits; temperature